Synthesis and Photocatalytic Activity of Hybrid Layered Zno(Myristic Acid)/Ag Nanoparticles - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
A new hybrid hetero nanocomposite, consisting of ZnO(myristic acid)/Ag-NPs, has been synthesized. The nanocomposite, made up of single ZnO nanosheets sandwiched between myristic acid self-assembled monolayers was synthesized and decorated with metal nanoparticles by chemical solution and tested in the photodegradation of methylene blue under UV light irradiation. The product displayed significant photocatalytic activity for degradation of the dye, and the activity was improved by a factor of three compared to bulk ZnO under similar conditions. The observed photodegradation efficiency is discussed in terms of the confinement of the semiconductor in the two dimensional structure, the adsorption ability of the organic component and the plasmonic absorption of Ag nanoparticles, which makes them act as electron wells, thus promoting charge separation and a reduced recombination rate. (C) 2016 Elsevier B.V. All rights reserved.